Engaging Patients in Primary Care Quality Improvement Initiatives: Facilitators and Barriers. (January 2020) - Pandhi, Nancy; Jacobson, Nora; Crowder, Madison; Quanbeck, Andrew; Hass, Mollie; Davis, Sarah
Health care transformation calls for patient engagement in quality improvement (PEQI), yet practice participation remains low. This pilot study of 8 primary care clinics at 7 statewide locations sought to determine the most effective strategies for disseminating a previously successful single-system PEQI intervention. Qualitative data were obtained through site visits, interviews, observations, and journaling. All material pertaining to barriers, recruitment/retention, and implementation was extracted, compared, and categorized. Five teams partially completed the intervention and 3 finished. These 3 teams did not ask for shorter trainings and were assigned a quality improvement (QI) coach. Multiple barriers to recruitment, implementation, and retention were noted at the organizational and clinic/team level, including turnover, shifting priorities, cross-level communication difficulties, lack of QI knowledge, and confusion between patient engagement and patient activation. These findings suggest that QI facilitation and dedicated time can help primary care teams identify and overcome barriers to PEQI.